Exposure to Cigarette Smoke in the Home and the Risk of Pneumonia in Toddlers in Indonesia: Systematic Study - Widiastuti, Yulia; Setiani, Onny; Budiyono, Budiyono (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2024)
Pneumonia is a respiratory disease that affects more than 287,000 children under five in Indonesia, with 444 deaths among those under five. One of the factors causing pneumonia is exposure to tobacco smoke in the home. This study aimed to describe the association between exposure to indoor tobacco smoke and the incidence of pneumonia among under-fives in Indonesia. This study method was a systematic review using articles from national and international journal databases. Databases used included Google Scholar, Garuda Portal, Scopus, Science Direct, ProQuest, and Springer Link. Articles in this study used the case-control method, published between 2013 and 2023, and focused on the association between indoor tobacco smoke exposure and under-five pneumonia incidence. There were 15 articles reviewed in this study. From the review of 15 articles, factors of exposure to secondhand smoke found in the home include the smoking habits of family members, the presence of family members who smoke, the number of family members who smoke, the location of smoking in the house, the presence of secondhand smoke exposure in the house, the number of cigarettes consumed by family members, the togetherness of infants with smokers, and the smoking status of the father. Most articles show a significant association between exposure to tobacco smoke in the home and the incidence of under-five pneumonia, so it can be concluded that exposure to tobacco smoke in the house is associated with pneumonia in under-fives.